Western Australian Midwives’ Perceptions and Experiences of Being ‘With Woman’ During Labour and Birth - Bradfield, Zoe (Curtin University, 2019)
Being ‘with woman’ is an important construct of the midwifery profession and is included in philosophy statements of leading midwifery organisations globally. Despite its centrality, little research has been conducted to offer evidence around this phenomenon. A phenomenological approach was undertaken to explore Western Australian midwives’ perceptions and experiences of being ‘with woman’ in a variety of models. Findings revealed that while midwives perceived the phenomenon similarly, experiences were distinct to the model worked in.